Influence of the Agreement on Enhancing International Arctic Scientific Cooperation on the approach of non-Arctic states to Arctic scientific activities - Han, Liu (Polar Research Institute of China - PRIC, 2018)
As the third legally-binding instrument of the Arctic Council, the Agreement on Enhancing International Arctic Scientific Cooperation was signed in May 2017 and entered into force on 23 May 2018. The Agreement not only reduces obstacles to the international scientific cooperation and promotes the movement of people and equipment across borders for the effective and efficient development of Arctic scientific knowledge, but also provides an improved international Arctic legal environment for conducting Arctic scientific cooperation based on UNCLOS and institutional arrangements. However, the observer states, the NGOs and IGOs, as well as Permanent Participants are rarely mentioned in this Agreement. This article chooses one group, non-Arctic states, as a case in point in order to critically discuss the influence of this new Arctic scientific cooperation agreement. It argues that the non-Arctic states are left behind at the original legal situation and trapped in an inferior status in Arctic science. Under these circumstances, this article suggests that non-Arctic states, especially those with competitive research abilities, should appeal for amendment of the Agreement to allow wider access to research areas and data sharing, especially when cooperating with the eight-member states of the Arctic Council. Also, non-Arctic states should take the Agreement as the reference when signing bilateral agreements with Arctic states so as to safeguard their interests when conducting Arctic scientific activities. Moreover, the active participation in other fora as well as various bilateral scientific projects can assist non-Arctic states to strengthen the relations with the Arctic states and build trust in the Arctic Council.